Primary Care Practice Workplace Social Capital: A Potential Secret Sauce for Improved Staff Well-Being and Patient Experience. (March 2019) - Perzynski, Adam T; Caron, Aleece; Margolius, David; Sudano, Joseph J
Patient experiences with the health-care system are increasingly seen as a vital measure of health-care quality. This study examined whether workplace social capital and employee outcomes are associated with patients' perceptions of care quality across multiple clinic sites in a diverse, urban safety net care setting. Data from clinic staff were collected using paper and pencil surveys and data from patients were collected via a telephone survey. A total of 8392 adult primary care patients and 265 staff (physicians, nurses, allied health, and support staff) were surveyed at 10 community health clinics. The staff survey included brief measures of workplace social capital, burnout, and job satisfaction. The patient-level outcome was patients' overall rating of the quality of care. Factor analysis and reliability analysis were conducted to examine measurement properties of the employee data. Data were aggregated and measures were examined at the clinic site level. Workplace social capital had moderate to strong associations with burnout ( r = −0.40, P < .01) and job satisfaction ( r = 0.59, P < .01). Mean patient quality of care rating was 8.90 (95% confidence interval: 8.86-8.94) ranging from 8.57 to 9.18 across clinic sites. Pearson correlations with patient-rated care quality were high for workplace social capital ( r = 0.88, P = .001), employee burnout ( r = −0.74, P < .05), and satisfaction ( r = 0.69, P < .05). Patient-perceived clinic quality differences were largely explained by differences in workplace social capital, staff burnout, and satisfaction. Investments in workplace social capital to improve employee satisfaction and reduce burnout may be key to better patient experiences in primary care.